Peningkatan Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti dengan Mengguanakan Media Interaktif di Kelas V SDN 24 Koto Raya Kabupaten Pesisir Selatan - Ruswandi, Ruswandi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve the learning outcomes and engagement of fifth-grade students at SDN 24 Koto Raya in Islamic Religious Education (PAI) lessons on the topic When Life Has Ended. This research employs Classroom Action Research (CAR) methodology with two cycles, involving four stages: planning, implementation, observation, and reflection. The results show that the application of interactive media and a discussion-based approach enhanced students’ learning outcomes, with mastery increasing from 60% in Cycle I to 87% in Cycle II. The use of interactive media made learning more engaging and encouraged active student participation. Therefore, interactive media proved effective in improving the quality of learning and student outcomes on the taught subject.